The Impact of E-Business Technologies and Social Media Marketing on Indonesian SMEs Sustainability - Prabowo, Hartiwi; Sriwidadi, Teguh (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: As a result of the COVID-19 pandemic, many MSMEs in Indonesia have experienced losses and some have even gone bankrupt. To try to keep their business running, MSMEs must carry out digital transformation, including by selling their merchandise via the internet, using social media such as Instagram and Facebook, as well as online markets including Tokopedia, Shopee, Bukalapak, Blibli, and Lazada. By using the internet for business, it is necessary to know the role of e-business technology and social media marketing. Therefore, this research examines how perceived usefulness, perceived ease of use, and digital transformation influence the sustainability of SMEs through e-business technology and social media marketing.Methodology: This research uses quantitative methods with a type of causal research. The population in this study were members of the CUP Bestari UKM community, numbering around 600 SMEs. To determine the sample size, the convenience sampling method was used, the sampling process was from the population closest and easiest to reach for researchers, taken from members of the CUP Bestari SMEs participating in the November 2021 bazaar at the Periuk District Hall, Tangerang City, totaling 108 samples. Primary data collection was carried out using a questionnaire by sending a Google Forms link to members of the UKM CUP Bestari community via WhatsApp. Then the data was analyzed using partial square rent structural equation modeling techniques. Finding:  As a result, perceived usefulness and perceived ease of use have a significant influence on e-business technology. Perceived ease of use significantly affects social media marketing, perceived usefulness does not affect social media marketing. In addition, e-business technology significantly influences SMEs' sustainability, and e-business technology also influences SMEs' sustainability. Perceived usefulness and perceived ease of use influence SME sustainability both through e-business technology and through social media marketing. Meanwhile, digital transformation does not influence social media marketing both direct and indirect through social media marketing as a mediator.Conclusion: SME sustainability is influenced by factors of perceived usefulness, and perceived ease of use with e-business technology, and social media marketing as mediating variables. Another factor, namely digital transformation does not influence social media marketing both directly and indirectly through social media marketing as a mediator. In future research, it is recommended to use digital transformation as a variable that moderates the achievement of SME sustainability.